(untitled) (Vietnam Journal of Catalysis and Adsorption, 2022)
We were synthesized CdSe nanocrystals (NC) at a temperature of 260 oC and controlling their growth kinetics follows different reaction times from 1 minute to 180 minutes. Base on their optical properties and estimated size to track their growth kinetics follow the Lamer model. Structure and morphology characterized were investigated by XRD pattern and transmission electron microscopy (TEM). All samples show cubic zinc blende type structures. The average NCs size can be calculated by absorption spectra, XRD and TEM, these results lie in close vicinity with each other. The energies of photoluminescence (PL) peaks and band gap of CdSe NCs can be tuned within the regions of 1.99 eV to 2.13 eV and 1.92 eV to 2.12 eV with increasing reaction time. The Stokes shifts and PL emission peaks are narrow, thus confirming the formation of uniformly distributed NCs.